Karakteristik Perpindahan Panas Alat Penukar Kalor Tipe Staggered Fins Berisi Material Fasa Berubah dari Minyak Kelapa pada Proses Pembekuan - Irsyad, Muhammad; Amrizal, Amrizal; Yulian, Aji Muhammad; Susila, M. Dyan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Indonesia, located in the tropics, has a dependency on air conditioners to obtain the thermal comfort of the room. This phenomenon resulted in the electricity consumption of the building increased significantly. On the other hand, Indonesia has the potential for cold air at night that is in the range of the thermal comfort temperature of the room or lower. The potential for cold air can be exploited by using Phase Change Material (PCM). Coconut oils are commodities that are widely produced in Indonesia. These materials have good potential to be developed as PCM because they have high latent heat and the temperature of phase change matches the temperature of the cold air at night. This research used a staggered fins type heat exchanger with a total of 39 pieces, mounted zig zag with the number of lines was 11. Fins were made of hollow aluminium with a size of 1x0.5 inches with a height of 150 mm. The PCMs used were coconut oil with a mass of 1.5 kg. The temperature and velocity of entering cold air were 20oC, 1 m/s, 2 m/s and 3 m/s. This study aims to determine the ability of PCM to release thermal so that it undergoes phase changes. The results showed that low cold airflow velocity resulted in subcooling while at 3 m/s, subcooling did not occur. The most considerable cooling rate occurred at 3 m/s that was 0.16oC/min. The percentage of solid mass formed after 60 minutes for each velocity was 37.8%, 58%, and 76.2%. The most considerable amount of heat absorbed by air was 167.7 kJ. Based on this, coconut oils are very potential to be developed by observing the temperature and velocity of the enter cold air.